Pengaruh Brand Image, Kepercayaan Merek dan Informasi Kemasan Produk Terhadap Keputusan Pembelian Produk Scarlett di Kota Batam - Adventina Evriati Sitorus; Realize (Komunitas Dosen Indonesia, 2024)
The main objective of this research is to explore the influence of brand image, brand trust, and product packaging information on purchasing decisions for Scarlett products in Batam City. This research is descriptive in nature and uses a quantitative approach for data collection and analysis. The population that is the research subject is Scarlett body lotion users in Batam City in 2024. To determine the sample size, the Jacob Cohen formula was used which resulted in a total of 204 respondents selected using the purposive sampling method. This research involves various tests, including data quality tests, classical assumption tests, influence tests, and hypothesis tests. The results of multiple linear regression analysis show that brand image contributes 14.2% to purchasing decisions. Meanwhile, brand trust contributed 28.9% to purchasing decisions, and product packaging information contributed 21.3% to purchasing decisions. Analysis of the coefficient of determination (R²) reveals that overall, variance in purchasing decisions can be explained by brand image, brand trust, and product packaging information with a total contribution of 63.3%. The results of the t test and F test show that brand image, brand trust, and product packaging information have a positive and significant influence, both partially and jointly, on purchasing decisions. These findings emphasize the importance of these factors in influencing consumer behavior in the context of purchasing Scarlett products in Batam City.